Analisis Strategi Pengembangan UMKM Berbasis Ekonomi Kreatif dalam Meningkatkan Ekonomi Masyarakat: Studi Kasus Penemuan Baru Usaha Pertamilk - Simamora, Vailimlim; Haliza, Nur; Simbolon, Irma Chintia; Dewi, Putri Kemala (Masyarakat Ekonomi Syariah Bogor, 2024)
This research examines the role of the creative economy in the development of Micro, Small and Medium Enterprises (MSMEs) in the City of Medan, Indonesia, with a focus on the Pertamilk business as a successful example of implementing creative economy-based strategies. Through a qualitative descriptive approach, primary data was obtained through interviews and observations of MSME actors who use the creative economy in their businesses. The research results show that the development of creative economy-based MSMEs has an important role in improving the community's economy. Pertamilk's business, with its product innovation and creative marketing, has succeeded in attracting customer interest and expanding market share. Pertamilk's success provides inspiration for other MSME players to continue to innovate and follow market trends. In this context, support and promotion from the government and society are very important to strengthen the creative economy-based MSME ecosystem. Through creativity, innovation and focus on quality, MSMEs can face competitive challenges and create a competitive advantage in an increasingly tight market.